STRATEGI PENGAWASAN PENYEDIAAN AIR MINUM DALAM RANGKA EFEKTIVITAS PEMANFAATAN SUMBER DAYA ALAM - Lina Lina (Program Studi Manajemen Lingkungan, 2017)
The water sector is a public service which has close links with poverty reduction. Inadequate infrastructure and facilities for drinking water and sanitation, especially in rural and suburban areas (peri-urban) adversely affect the health and environmental conditions that have a continuing impact on the level of the family economy. Provision of drinking water infrastructure and improved sanitation will have an impact on improving the quality of the environment and public health, and time can be saved from efforts to obtain drinking water and good sanitation. The third impact will further impact the community in the form of increased productivity. Theaim of this study include(1.) To determine the effectiveness of the management of drinking water supply systems in rural communities basedPamsimas receiver in the district. (2.) To find out the various components that can affect the effectiveness of water supply systems in rural communities based mimum Pamsimas receiver in the district. The method used in this is for descriptive theoretical research.conclusionIf the drinking water supply control strategies implemented in accordancewith thefunctionmanajememenuseofnatural resourceswill be effective in order to meet the water needs of the community . From the results of this study should be carried out supervisory functions of planning to terbangunya means awall should start from the village level to the district level (government departments associated with drinking water peyediaan). Water Agency business does not just manage the financial system alone , fermented well functioning and sustainability of facilities ( From spring to prime the public water distribution ) . Management of the environment is also a shared responsibility of theuser and BPSPM Preferably in the springs need for regular supervision so awake kelestarianya sehinngga water discharge can be maintained.